2005
DOI: 10.1179/136485905x29675
|View full text |Cite
|
Sign up to set email alerts
|

Bancroftian filariasis: patterns of vector abundance and transmission in two East African communities with different levels of endemicity

Abstract: Intensive monitoring of Wuchereria bancrofti vector abundance and transmission intensity was carried out in two communities, one with high-level endemicity for bancroftian filariasis (Masaika, Tanzania) and the other with low-level (Kingwede, Kenya), on the East African coast. Mosquitoes were collected in light traps, from 50 randomly selected households in each community, once weekly for 1 year. They were identified, dissected and checked for parity and filarial larvae. Anopheles gambiae s. l., An. funestus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…A longitudinal entomological survey was carried out in 50 randomly selected houses for 1 year, from July 1998 to June 1999, as described by Rwegoshora et al (2005). Briefly, in each selected house, a batteryoperated CDC light trap was placed, on one night each week, beside an occupied bed provided with an un-impregnated mosquito net.…”
Section: Entomological Surveillancementioning
confidence: 99%
See 2 more Smart Citations
“…A longitudinal entomological survey was carried out in 50 randomly selected houses for 1 year, from July 1998 to June 1999, as described by Rwegoshora et al (2005). Briefly, in each selected house, a batteryoperated CDC light trap was placed, on one night each week, beside an occupied bed provided with an un-impregnated mosquito net.…”
Section: Entomological Surveillancementioning
confidence: 99%
“…The results of several studies on bancroftian filariasis in coastal East Africa have shown that the human infection and disease burden vary considerably from one community to the other within the same endemic area (White, 1971;Wijers, 1977;McMahon et al, 1981;Meyrowitsch et al, 1995;Simonsen et al, 1995;Wamae et al, 1998;Mukoko et al, 2004). In a study recently carried out in a community of high endemicity and another of low endemicity, both in coastal East Africa, it was found that the much higher intensity of transmission and rates of human infection and disease seen in the highly endemic community were clearly associated with considerably higher vector densities (Simonsen et al, 2002;Rwegoshora et al, 2005), and that the differences in level of endemicity appeared to result primarily from differences in the mosquito breeding habitats in the two communities.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Briefly, in Masaika and Kingwede there were 950 and 1,013 inhabitants who were 1 year old or older; the overall mf prevalence and the overall CFA prevalence in these individuals were 25.5 and 52.2%, respectively, in Masaika and 2.9% and 16.4%, respectively, in Kingwede. Thus, the prevalence of lymphatic filariasis was higher in Masaika than in Kingwede, a fact that was reflected in a much higher level of transmission in Masaika than in Kingwede (the annual transmission potentials were 92.9 and 6.4, respectively, during the year preceding the surveys reported here [39]). The study was approved by the Medical Research Coordinating Committee of the National Institute for Medical Research, Tanzania, the Kenyatta National Hospital Ethical and Research Committee, Kenya, and the Central Scientific-Ethical Committee, Denmark.…”
Section: Methodsmentioning
confidence: 94%
“…We present here results from one such comparative immunoepidemiological analysis in which we focused on comparing observed age relationships between filarial specific antibody responses and W. bancrofti intensity in a community with low parasite transmission intensity in coastal East Africa with the relationships observed in a community in the same region with a higher transmission intensity (25,39,43). One feature of the analyses reported here was the use of a combined empirical data analysis and mathematical modeling approach for investigating mechanisms that may underlie the observed differences in the age patterns of parasite-specific antibody responses between communities exposed to different transmission pressures (24,25,50,51).…”
mentioning
confidence: 99%